Governing transfer pricing aggressiveness in Indonesia: A systematic review of tax regulatory design and enforcement challenges - Supriyadi, Supriyadi; Kusuma, I Gede Komang Chahya Bayu Anta (Educoretax, 2025)
Transfer Pricing Aggressiveness continues to provide a significant difficulty within Indonesia's Tax System, leading to base erosion, tax disputes, and legal ambiguity. This study seeks to reconceptualize transfer pricing aggression as a governance issue by identifying fundamental structural flaws and offering evidence-based policy remedies that fit with challenges in tax regulatory design and enforcement, in contrast to previous research that mostly concentrated on firm-level factors. This study utilizes a qualitative methodology grounded in a systematic literature survey of peer-reviewed international and national journals, supplemented by a comprehensive analysis of Indonesia's transfer pricing regulations. The literature is examined thematically to identify repeating trends in supervision, audit techniques, and dispute settlement, thus merging empirical findings with regulatory viewpoints. The findings indicate that transfer pricing aggression in Indonesia is perpetuated not just by business motivations to reduce tax liabilities but also by disjointed risk assessment, unreliable auditing practices, restricted access to dependable comparables, and reactive dispute resolution mechanisms. The discourse reveals that a discrepancy between regulatory goal and administrative capability exacerbates conflicts and undermines legal certainty, while inadequately coordinated oversight diminishes the efficacy of transfer pricing regulation. These governance deficiencies interact with corporate incentives, exacerbating antagonistic conduct and heightening the probability of extended conflicts. The report indicates that reducing transfer pricing aggressiveness necessitates a comprehensive governance strategy that integrates regulatory clarity, risk-based oversight, consistent auditing, advanced data infrastructure, and proactive dispute resolution processes. The results provide pertinent insights for tax authorities and enhance the literature by establishing a cohesive framework for regulating transfer pricing aggression in developing nations.